3D concrete printing with cement-coated recycled crumb rubber: Compressive and microstructural properties. (12th September 2022) - Liu, Junli; Setunge, Sujeeva; Tran, Phuong
Highlights: Recycled crumb rubber is coated with cement paste via a ball milling machine. Three weight ratios of cement to rubber are designed for different coating quality. X-ray micro-computed tomography is used to analyse pores and crack propagation. Degree of increase in compressive strength relies on the coating quality of rubber. Anisotropic compressive property is primarily related to pore shape and orientation. Abstract: The modification of a rubber surface, such as cement coating, is an effective method for enhancing the mechanical performance of concrete containing recycled rubber particles. Although this method has been widely investigated for cast concrete, there is limited research on 3D-printed cementitious materials. This study explored the correlation between the compressive strength and microstructural property of 3D-printed rubberised mortar with cement-coated crumb rubber (15 wt% replacement of river sand). Multiple ratios of cement-to-rubber (C/R) were designed to achieve different coating qualities, including C/Rs of 0.25 (CR-0.25), 0.4 (CR-0.4) and 0.55 (CR-0.55). Scanning electron microscopy (SEM) images showed the existence of hardened cementitious shells outside the rubber particles, which effectively improved the interfacial bonding between the rubber surface and the cement matrix. The compressive strengths of the printed specimens did not always improve as the ratio of cement to rubber for coating increased. Moreover, the anisotropy in compressive strength was more obvious in the CR-0.4 and CR-0.55, where the strength in the Y (printing) direction was about 7 % higher than that observed in the Z (layer deposition) direction. X-ray micro-computed tomography (μCT) analysis revealed that the mechanical anisotropy in CR-0.4 and CR-0.55 could be primarily attributed to two factors – pore morphology and pore orientation relative to the external loading direction. For CR-0.25, the rubber-to-matrix interface bonding appeared more critical for the compressive strength. Finally, the printed specimens showed the higher compressive strengths than the cast ones due to the lower fraction of large pores (diameters ≥ 1 mm).